Expert Judgment for Climate Change Adaptation. Issue 5 (December 2016) - Thompson, Erica; Frigg, Roman; Helgeson, Casey
Abstract : Climate change adaptation is largely a local matter, and adaptation planning can benefit from local climate change projections. Such projections are typically generated by accepting climate model outputs in a relatively uncritical way. We argue, based on the IPCC's treatment of model outputs from the CMIP5 ensemble, that this approach is unwarranted and that subjective expert judgment should play a central role in the provision of local climate change projections intended to support decision-making.